The Effect of α-lipoic Acid on C-Reactive Protein Level: A Meta-analysis of Randomized, Double-Blind, and Placebo-Controlled Studies. Issue 3 (30th September 2022) - Đukić, Ljiljana; Trajković, Lazar; Knežević, Tamara; Dimitrijević, Jelena; Krstić, Danijela; Stojanović, Marko
The C-reactive protein is generally considered a marker of inflammation, and it is widely used in clinical practice as a minimally invasive index of any ongoing inflammatory response. Alpha-lipoic acid (ALA) supplementation can be beneficial for human health, especially in the sense of its anti-inflammatory action. The aim of this meta-analysis was to, based on the currently available highest level of evidence (prospective, randomized, double-blind, and placebo-controlled data), investigate the effect of ALA supplementation on CRP levels. Prospective, randomized, double-blind, and placebo-controlled clinical trials were extracted after a systematic search of PubMed, the Cochrane Library, the Web of Science, EMBASE, and the Scopus databases. A random effect model was used in this meta-analysis to investigate the influence of ALA on the blood CRP level. The subgroup analysis and meta-regression were used to identify the source of heterogeneity. This meta-analysis provided evidence of the positive effect of ALA on the reduction of the blood CRP level. The subgroup analysis and meta-regression results indicated that ALA can reduce the CRP level when administrated at a 600 mg dose, and not in higher or lower doses. Also, a shorter duration of study positively correlates with the reduction of CRP after ALA supplementation.